Induction Coils for Measuring Low Frequency and Low Intensity Magnetic Fields - Milić, Saša (Proceedings, Electrical engineering institute "Nikola Tesla", 2020)
Short air core induction coils with a large radius and a large number of turns can be successfully used as induction sensors for detecting low-intensity quasistationary magnetic fields, such as magnetic fields of ships. The application of these sensors is presented in detail, and then a practical methodology for determining all the necessary parameters of the sensor is proposed. The sensitivity of sensors with real numbers is determined and inductance is calculated in several ways. The practical results of ship’s magnetism measurement and the calculation of all parameters of the coil are presented. A comparative analysis of all results was performed and the observed deviations were thoroughly commented on.